KELENGKAPAN PENDOKUMENTASIAN SERTIFIKAT MEDIS PENYEBAB KEMATIAN DAN AKURASI PENYEBAB DASAR KEMATIAN - titin wahyuni; Dyah Rachmadhani (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Medical certification of cause of death (MCCD) is being issued on every death insident in every hospital of Indonesia. MCCD consists of two part; part 1 would record with those conditions in the causal link that leading to death and part 2 would fill with other condition that significant in contributing to death. Leading cause of death are defined as Underlying Cause of  Death  (UCoD). The quality of it may varies considering to a medically qualified doctor who record it. This study aims to determine the completeness of MCCD and the accuracy of UCoD. The research design used was non experimental with retrospective approach. The sample in this study is Medical certification of cause of death in January to April 2017; 106. Large MCCD classified as incomplete that is equal to 45,28% and from 55,17% categorized not accurate. The conclusion of this research is that the incomplete SMPK will not apply.